2014
DOI: 10.1002/2014jc010123
|View full text |Cite
|
Sign up to set email alerts
|

Convective instability in sedimentation: 3-D numerical study

Abstract: To provide a probable explanation on the field observed rapid sedimentation process near river mouths, we investigate the convective sedimentation in stably stratified saltwater using 3-D numerical simulations. Guided by the linear stability analysis, this study focuses on the nonlinear interactions of several mechanisms, which lead to various sediment finger patterns, and the effective settling velocity for sediment ranging from clay (single-particle settling velocity V 0 5 0.0036 and 0.0144 mm/s, or particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 31 publications
(64 reference statements)
2
46
0
Order By: Relevance
“…The initial studies of Burns and Meiburg [2012] and Yu et al [2013] both suggested that when the Stokes diameter of the sediment in the freshwater layer is greater than approximately 10 lm, it is likely that settling-driven convection will dominate at isothermal conditions under salt induced stratification. The 3-D simulations of Yu et al [2014] for three different particles sizes (2, 4, and 20 lm) under a range of concentrations (4-32 g/L) confirmed and further teased out the conditions that will lead to different instability modes by showing that for unflocculated clay (d5 2-4 lm) salt stratification at isothermal conditions should lead to double-diffusive dominated instabilities. However, as sediment size shifts up into the silt range (d 5 20 lm), the dominant mode shifts toward settling driven leaking.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 66%
See 4 more Smart Citations
“…The initial studies of Burns and Meiburg [2012] and Yu et al [2013] both suggested that when the Stokes diameter of the sediment in the freshwater layer is greater than approximately 10 lm, it is likely that settling-driven convection will dominate at isothermal conditions under salt induced stratification. The 3-D simulations of Yu et al [2014] for three different particles sizes (2, 4, and 20 lm) under a range of concentrations (4-32 g/L) confirmed and further teased out the conditions that will lead to different instability modes by showing that for unflocculated clay (d5 2-4 lm) salt stratification at isothermal conditions should lead to double-diffusive dominated instabilities. However, as sediment size shifts up into the silt range (d 5 20 lm), the dominant mode shifts toward settling driven leaking.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 66%
“…This produces an unstable band of sediment-laden saltwater, i.e., the so-called interface layer, sitting between the muddy freshwater and the underlying clear saltwater. This phenomenon has been experimentally observed by Hoyal et al [1999b], Parsons et al [2001], and Blanchette and Bush [2005] and examined through linear stability analysis by Burns and Meiburg [2012] and Yu et al [2013] and Direct Numerical Simulation (DNS) by Yu et al [2014] and Burns and Meiburg [2015]. A few defining characteristics of the settlingdriven mechanism are the general creation of the interface layer below the initial stratification contact [Hoyal et al, 1999b], the onset of Rayleigh-Taylor generated plume like structures, asymmetry in the downward and upward interface motions, and the overall larger length scales of the instabilities and instabilities spacing (centimeter scale) compared to the double-diffusive generated fingering (millimeter scale) [Hoyal et al, 1999b;Blanchette and Bush, 2005;Burns and Meiburg, 2012;Yu et al, 2013;Burns and Meiburg, 2015;Yu et al, 2014].…”
Section: Interface Instabilities In the Absence Of Turbulent Mixingmentioning
confidence: 92%
See 3 more Smart Citations